2019
DOI: 10.1002/med.21584
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome interventions in human health and diseases

Abstract: Ongoing studies have determined that the gut microbiota is a major factor influencing both health and disease. Host genetic factors and environmental factors contribute to differences in gut microbiota composition and function. Intestinal dysbiosis is a cause or a contributory cause for diseases in multiple body systems, ranging from the digestive system to the immune, cardiovascular, respiratory, and even nervous system. Investigation of pathogenesis has identified specific species or strains, bacterial genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 260 publications
(451 reference statements)
0
42
0
1
Order By: Relevance
“…Since the gut microbiota affects inflammation and immunity not only locally at the mucosal level but also systemically, it stands to reason that the dysbiosis of gut microbiota should exist in various diseases, including brain disorders. 4 Patients with Parkinson's disease who suffer from constipation exhibit an altered gut microbiota with increased Enterobacteriaceae and decreased Prevotella, which is related to motor phenotype in patients. 5 In individuals with Alzheimer's disease, the altered microbiota is characterized by increased Bacteroidetes, decreased Firmicutes and Bifidobacterium.…”
Section: Introductionmentioning
confidence: 99%
“…Since the gut microbiota affects inflammation and immunity not only locally at the mucosal level but also systemically, it stands to reason that the dysbiosis of gut microbiota should exist in various diseases, including brain disorders. 4 Patients with Parkinson's disease who suffer from constipation exhibit an altered gut microbiota with increased Enterobacteriaceae and decreased Prevotella, which is related to motor phenotype in patients. 5 In individuals with Alzheimer's disease, the altered microbiota is characterized by increased Bacteroidetes, decreased Firmicutes and Bifidobacterium.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors can modulate the profile of gut microbiota. This includes genetic and environmental factors along with baseline intestinal and generic health [10]. The diversity and composition of gut microbes is dynamic with antibiotic usage, obesity, allergies, inflammatory diseases and metabolic conditions, such as diabetes and cardiovascular diseases, all known to influence the ecosystem of the gut [11].…”
Section: Introductionmentioning
confidence: 99%
“…These bacteria are involved in bile acid metabolism, i.e., to generate bile salt hydrolase (BSH) enzymes that reduce cholesterol level [54]. Obese human subjects showed a higher Firmicutes/Bacteroidetes ratio after supplementation with polyphenols, and this has been proposed as a reason for weight loss [92,93]. A previous study showed that body weight and dramatic dietary patterns might affect the gut microbiota composition [94,95].…”
Section: Discussionmentioning
confidence: 99%